Analisis Perbandingan Kecepatan Deploy Container Orchestration Menggunakan Docker Swarm dan Kubernetes - Umam, Chaerul; Ervikhan, Muhammad Ibnu (Jurnal Transformatika, 2023)
A good infrastructure is to be able to provide services with high capability for its clients. The infrastructure of a server is said to be good if it can handle many requests from clients and does not experience downtime. The speed of deploying on container orchestration-based infrastructure greatly affects the downtime of a system. The author uses the Docker Swarm and Kubernetes to compare the deployment speed to find good performance and is suitable. The result shows that Kubernetes has a faster deploy speed than Docker Swarm. Docker Swarm gets an average speed for deploying 3 to 30 replications in 10 consecutive tests for 1 minute 9 seconds. Meanwhile, Kubernetes gets an average deploy speed of 1 minute 2 seconds.